Generic hardness of the Boolean satisfiability problem - Rybalov, Alexander (Groups, complexity, cryptology, 2017)
It follows from the famous result of Cook about the NP-completeness of the Boolean satisfiability problem that there is no polynomial algorithm for this problem if . In this paper, we prove that the Boolean satisfiability problem remains computationally hard on polynomial strongly generic subsets of formulas provided and . Boolean formulas are represented in the natural way by labeled binary trees.